1997
DOI: 10.1182/blood.v89.12.4385
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of Protein Tyrosine Phosphorylation in Thrombasthenic Platelets: Evidence That Phosphorylation of Cortactin and a 64-kD Protein Is Dependent on Thrombin Activation and Integrin αIIbβ3

Abstract: Tyrosine phosphorylation of a number of platelet proteins is dependent on platelet integrin αIIbβ3 (also termed GPIIb-IIIa) and its engagement in aggregation. For instance, in type I thrombasthenic platelets, which lack αIIbβ3 and do not aggregate, several substrates are either poorly or not phosphorylated. We have compared thrombasthenic platelets of type I, type II (15% αIIbβ3, functional), and variant type (50% αIIbβ3, no fibrinogen binding). The platelets from the three patients exhibited the same low tyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 26 publications
5
14
0
Order By: Relevance
“…However, cortactin (80 kDa) was still phosphorylated in the early stages after 2-MeS-ADP stimulation whereas the second wave of phosphorylation was inhibited ( Figs 4C and 5C). This observation is in accordance with our previous results: (i) when control platelets were stimulated with thrombin in the presence of RGDS; (ii) when we used platelets from Glanzmann's thrombasthenia patients, indicating that the second wave of phosphorylation of cortactin definitely depends on GPIIb/IIIa engagement (Rosa et al, 1997).…”
Section: Kinetics Of 2-mes-adp-induced Tyrosine Phosphorylations Befosupporting
confidence: 93%
“…However, cortactin (80 kDa) was still phosphorylated in the early stages after 2-MeS-ADP stimulation whereas the second wave of phosphorylation was inhibited ( Figs 4C and 5C). This observation is in accordance with our previous results: (i) when control platelets were stimulated with thrombin in the presence of RGDS; (ii) when we used platelets from Glanzmann's thrombasthenia patients, indicating that the second wave of phosphorylation of cortactin definitely depends on GPIIb/IIIa engagement (Rosa et al, 1997).…”
Section: Kinetics Of 2-mes-adp-induced Tyrosine Phosphorylations Befosupporting
confidence: 93%
“…In thrombasthenic platelets, the time-dependent translocation of tyrosinephosphorylated proteins to the cytoskeleton was also observed upon platelet activation. However, lower amounts of most of the proteins were detected as less tyrosine phosphorylation of the proteins occurred in these platelets, as shown by the analysis of the corresponding Triton X-100-soluble protein fractions and as also reported previously by others [36,39]. The presence of the tyrosine kinases Src, Syk and FAK and the lipid and tyrosine kinase PI-3K along with tyrosine-phosphorylated proteins was detected in the actin cytoskeleton from αIIbβ3and CD36deficient platelets ( Figure 7B).…”
Section: Translocation Of Signalling Proteins Into the Tsp-1-enrichedsupporting
confidence: 87%
“…However, macroscopic aggregation did not occur when the patient's platelets were stirred with thrombin (Chen et al, 1992). This was independently confirmed for this patient by Rosa et al (1997), who showed that addition of thrombin in stirred platelet suspensions was not followed by aggregation-dependent tyrosine phosphorylations. Why does aggregation not occur?…”
Section: Discussionmentioning
confidence: 52%